Αριθμητική διερεύνηση του ελάχιστου πάχους αποβλίττου στις κατεργασίες αποβολής υλικού - Βαρελτζής, Δημήτρης (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Μηχανολόγων Μηχανικών, 2015)
The Aim of this thesis is to conduct nanoscale cutting by means of molecular dynamics simulations. So initially the theoretical base of the model of Molecular Dynamics and specifically all its fundamental factors were presented, such as calculations of the atoms’ trajectories, the selection of potential energy function and selection of the cutting speed. In the next chapter, Molecular Dynamics in nanoscale cutting processes, its advantages, limitations and the main parameters, such as the selection of diatomic potential, the change in rake angle the cutting depth and the edge radius are analyzed. Also, in the context of the completion of the literature review, various studies that focused on variation of the cutting depth and edge radius, and the way they are associated with the minimum chip thickness., are presented. The following chapter includes the computational part of this diploma thesis, which refers to the Matlab code and the additions made to incorporate the rake angle, cutting depth and the edge radius. Then simulations were conducted by varying the aforementioned parameters and investigate the minimum chip thickness. Finally, the conclusions from the simulations were drawn and some future prospects for the continuation of research in this area were listed.